A randomized trial of adjunct testosterone for cancer‐related muscle loss in men and women. Issue 3 (14th April 2018) - Wright, Traver J.; Dillon, E. Lichar; Durham, William J.; Chamberlain, Albert; Randolph, Kathleen M.; Danesi, Christopher; Horstman, Astrid M.; Gilkison, Charles R.; Willis, Maurice; Richardson, Gwyn; Hatch, Sandra S.; Jupiter, Daniel C.; et al.
Abstract: Background: Cancer cachexia negatively impacts cancer‐related treatment options, quality of life, morbidity, and mortality, yet no established therapies exist. We investigated the anabolic properties of testosterone to limit the loss of body mass in late stage cancer patients undergoing standard of care cancer treatment. Methods: A randomized, double‐blind, placebo‐controlled phase II clinical trial was undertaken to assess the potential therapeutic role of adjunct testosterone to limit loss of body mass in patients with squamous cell carcinoma of the cervix or head and neck undergoing standard of care treatment including chemotherapy and chemoradiation. Patients were randomly assigned in blocks to receive weekly injections of either 100 mg testosterone enanthate or placebo for 7 weeks. The primary outcome was per cent change in lean body mass, and secondary outcomes included assessment of quality of life, tests of physical performance, muscle strength, daily activity levels, resting energy expenditure, nutritional intake, and overall survival. Results: A total of 28 patients were enrolled, 22 patients were studied to completion, and 21 patients were included in the final analysis (12 placebo, nine testosterone). Adjunct testosterone increased lean body mass by 3.2% (95% confidence interval [CI], 0–7%) whereas those receiving placebo lost 3.3% (95% CI, −7% to 1%, P  = 0.015). Although testosterone patients maintained more favourable body condition, sustained daily activity levels, and showed meaningful improvements in quality of life and physical performance, overall survival was similar in both treatment groups. Conclusions: In patients with advanced cancer undergoing the early phase of standard of care therapy, adjunct testosterone improved lean body mass and was also associated with increased quality of life, and physical activity compared with placebo.